Reorganizing Italy’s Territorial Healthcare: the Ministerial Decree No. 77/2022 and its Comparative Significance - Vinceti, S. R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
As approved by the European Commission in 2021, Italy’s National Recovery and Resilience Plan encompasses a far-reaching reform in the governance and structure of the national health service (NHS) that should shift the focus of assistance from large, centralized hospitals to a tight network of numerous smaller health centers dislocated in the country. In this respect, the adoption of the Ministerial Decree no. 77 on May 23, 2022, represented a key step in the execution of the intended reform, to the extent that the Decree set forth the main terms of the primary care reorganization process. This review summarizes the key elements of the Decree, foreshadows its legal and public health implications, acknowledges the uncertainties about the economic feasibility of the reform, and highlights its possible comparative significance for health systems facing similar challenges, especially those — such as the UK NHS — that share a comparable type of funding system and organizational framework.